2021
DOI: 10.1371/journal.pone.0249879
|View full text |Cite
|
Sign up to set email alerts
|

Journal article publishing in the social sciences and humanities: A comparison of Web of Science coverage for five European countries

Abstract: This study compares publication pattern dynamics in the social sciences and humanities in five European countries. Three are Central and Eastern European countries that share a similar cultural and political heritage (the Czech Republic, Slovakia, and Poland). The other two are Flanders (Belgium) and Norway, representing Western Europe and the Nordics, respectively. We analysed 449,409 publications from 2013–2016 and found that, despite persisting differences between the two groups of countries across all disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…However, in the CEE region, Poland and the Czech Republic were pioneers in international collaboration, number of articles published in foreign journals, citation impact, publication practices, and intensity of changes (Kozak, Bornmann, and Leydesdorff 2015). Recent studies have shown that publication patterns in political science and international relations in CEE countries have evolved toward publishing of articles in journals with greater citation impact, as indexed in the Web of Science (WoS) and Scopus (Korytkowski and Kulczycki 2019; Kulczycki et al 2018; Petr et al 2021). Figure 1 confirms these changes.
Figure 1 Total Number of Published Articles in Political Science and International Relations (Scopus 2005, 2010, 2015, 2020) Source: Scimago Journal & Country Rank (2021).
…”
Section: Shaping the Visibility Of Research By Changing Publication P...mentioning
confidence: 99%
“…However, in the CEE region, Poland and the Czech Republic were pioneers in international collaboration, number of articles published in foreign journals, citation impact, publication practices, and intensity of changes (Kozak, Bornmann, and Leydesdorff 2015). Recent studies have shown that publication patterns in political science and international relations in CEE countries have evolved toward publishing of articles in journals with greater citation impact, as indexed in the Web of Science (WoS) and Scopus (Korytkowski and Kulczycki 2019; Kulczycki et al 2018; Petr et al 2021). Figure 1 confirms these changes.
Figure 1 Total Number of Published Articles in Political Science and International Relations (Scopus 2005, 2010, 2015, 2020) Source: Scimago Journal & Country Rank (2021).
…”
Section: Shaping the Visibility Of Research By Changing Publication P...mentioning
confidence: 99%
“…As a consequence of the limitations enacted by both intrinsic and extrinsic factors, it is more difficult to comprehensively index the humanities via citations, a condition that limited the use of quantitative bibliometric methods in this area [24], despite clear progress over recent time [25,26]. The lack of a comprehensive and reliable citation index remains a known and open problem in the humanities [27][28][29].…”
Section: Citation Indexing and The Humanitiesmentioning
confidence: 99%
“…As a consequence of the limitations enacted by both intrinsic and extrinsic factors, it is more difficult to comprehensively index the humanities via citations, a condition that limited the use of quantitative bibliometric methods in this area [23], despite clear progress over recent time [24,25]. The lack of a comprehensive and reliable citation index remains a known and open problem in the humanities [26][27][28].…”
Section: Citation Indexing and The Humanitiesmentioning
confidence: 99%